Characterization of Lead Adherence Using Intravascular Ultrasound to Assess Difficulty of Transvenous Lead Extraction. (August 2020) - Beaser, Andrew D.; Aziz, Zaid; Besser, Stephanie A.; Jones, Christopher I.; Jameria, Zenith; Kannan, Arun; Upadhyay, Gaurav A.; Broman, Michael T.; Ozcan, Cevher; Tung, Roderick; Nayak, Hemal M.
Abstract : Background: Clinical factors associated with development of intravascular lead adherence (ILA) are unreliable predictors. Because vascular injury in the superior vena cava-right atrium during transvenous lead extraction is more likely to occur in segments with higher degrees of ILA, reliable and accurate assessment of ILA is warranted. We hypothesized that intravascular ultrasound (IVUS) could accurately visualize and quantify ILA and degree of ILA correlates with transvenous lead extraction difficulty. Methods: Serial imaging of leads occurred before transvenous lead extraction using IVUS. ILA areas were classified as high or low grade. Degree of extraction difficulty was assessed using 2 metrics and correlated with ILA grade. Lead extraction difficulty was calculated for each patient and compared with IVUS findings. Results: One hundred fifty-eight vascular segments in 60 patients were analyzed: 141 (89%) low grade versus 17 (11%) high grade. Median extraction time (low=0 versus high grade=97 seconds, P <0.001) and median laser pulsations delivered (low=0 versus high grade=5852, P <0.001) were significantly higher in high-grade segments. Most patients with low lead extraction difficulty score had low ILA grades. Eighty-six percentage of patients with high lead extraction difficulty score had low IVUS grade, and the degree of transvenous lead extraction difficulty was similar to patients with low IVUS grades and lead extraction difficulty scores. Conclusions: IVUS is a feasible imaging modality that may be useful in characterizing ILA in the superior vena cava-right atrium region. An ILA grading system using imaging correlates with extraction difficulty. Most patients with clinical factors associated with higher extraction difficulty may exhibit lower ILA and extraction difficulty based on IVUS imaging. Abstract : Supplemental Digital Content is available in the text.